Outdoor Learning Model Based on Traditional Balinese Games to Improve Cultural Literacy in Class V Social Studies Content - Aryanti, Kadek Cahya Hindira; Wulandari, I Gusti Agung Ayu (Jurnal Pendidikan Multikultural Indonesia, 2024)
The low cultural understanding is caused by the decline in reading interest of the Indonesian people. This type of research is a pseudo-experiment and the research design used is an unequal post-test control group design. The population is all 151 students in grade V of SD Group VI Abiansemal for the 2024/2025 school year. The sample determination technique uses cluster random sampling so that the samples obtained in this study are class V SD No. 1 Mambal as many as 22 students as an experimental group and class V SD No. 4 Mekar Bhuana as many as 11 students as a control group. Data collection uses the usual multiple-choice test and is analyzed by the Polled Variance t-test. The results of the hypothesis test show that the tcount result = 4.411 > ttable = 2.04 with a significance level of 5% and dk = 31. Based on the results of the analysis, there was a significant difference in the cultural literacy competence of the group of students who were taught with  the outdoor learning model  based on traditional Balinese games and the group of students who were taught with the conventional model. It can be concluded that  the  outdoor learning model  based on traditional Balinese games has an effect on improving the cultural literacy competence of grade V students of SD Cluster VI Abiansemal for the 2024/2025 school year. This model can be used by teachers in social studies teaching activities to help students develop cultural literacy competencies.